Imagining socioecological transformation: An analysis of the Welsh Government’s policy innovations and orientations to the future - Anna Pigott (Elememta: Science of the Anthropocene, 2018)
This article explores how the Welsh Government’s recent policy innovations in climate change and environmental sustainability can be read in terms of their imaginative capacity for transformation. The Welsh Government is one of only a few governments in the world to have a legal duty to sustainable development, which includes the pioneering Well-being of Future Generations Act (2015). The legislation has received international attention and praise from the United Nations but, as yet, the Welsh Government’s imaginaries of socioecological transformation have received little scrutiny regarding the kinds of ideas about the future and possibilities for change they set in motion. The article considers imaginaries as providing the very grounds of possibility for transformation, being comprised of stories and narratives about what kinds of futures are possible and desirable, intermingled with emotional-affective “atmospheres” that can promote or hinder people’s engagement with environmental issues. The article focuses on three aspects of the Welsh Government’s imaginaries related to socioecological transformation, namely; resilience and anticipatory discourse, linear time, and “conspiracies of optimism”. A number of tensions are drawn out that highlight how the Welsh Government’s seemingly progressive rhetoric risks being undermined by the conceptions of time and change it employs. Thus, the article contributes to wider critical analyses of how new politics and modes of governance of and for the (proposed) Anthropocene are taking shape.